Letter to the Editor Regarding: “Association Between Metabolic Score for Insulin Resistance (METS-IR) and Risk of Obstructive Sleep Apnea: Analysis of NHANES Database and a Chinese Cohort” [Response to Letter] - Zhou B; Yao Y; Wang Y; Yue W; Zhang J; He Y; Zhang Q; Wang Y; Hu K (Nature and Science of Sleep, 2025)
Beini Zhou,1,* Yan Yao,2,* Yuhan Wang,1 Wuriliga Yue,1 Jingyi Zhang,1 Yang He,1 Qingfeng Zhang,1 Yixuan Wang,1 Ke Hu1 1Department of Respiratory and Critical Care Medicine, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China; 2Department of Pharmacy, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ke Hu, Department of Respiratory and Critical Care Medicine, Renmin Hospital of Wuhan University, 238 Jiefang Street, Wuhan, 430060, People’s Republic of China, Email huke-rmhospital@163.com